No stone technology: Revolutionizing denim wash for sustainable fashion - Nahid-Ull-islam; Maruf Hasan Shah; Akter Mahmuda; Shahidul Islam Sakib; Kamrul Hassan Chowdhury (Tekstilna industrija)
The denim sector has to deal with secondhand trash, unsalable inventory, and processed waste. Although the process of recycling garbage is sustainable, it is not. Enthusiasts can use zero water technologies, ozone washes, stone-free technology, less hazardous dyeing and washing techniques, and advanced organic denim to enhance the denim experience. By transforming the way denim is treated, this technology may enhance worker safety and the environment NoStone® technology eliminates pumice stone in washing machines, offering a reusable, robust solution with easy-lock features, eliminating pollutants from extraction, transportation, and processing, and being lightweight and sustainable. This paper's primary goals are to examine water consumption and carbon footprint utilizing the no-stone approach and the ETP value for sustainability evaluation. This research also shows the sample's appearance before and following a stone-free wash. The denim's characteristics and aftercare cycle evaluation are also examined using a range of tests.